To simplify \( 1,000^{23} \), we first rewrite \( 1,000 \) in terms of base \( 10 \):
\[ 1,000 = 10^3 \]
Now, we can raise \( 1,000 \) to the power of \( 23 \):
\[ 1,000^{23} = (10^3)^{23} \]
Using the power of a power property of exponents, we multiply the exponents:
\[ (10^3)^{23} = 10^{3 \cdot 23} = 10^{69} \]
Now we can see what each person claimed:
- Charles claims \( 1,000^{23} = 10 \) (incorrect)
- Zayeer claims \( 1,000^{23} = 1,000 \) (incorrect)
- Kali claims \( 1,000^{23} = 100 \) (incorrect)
Since the correct simplification is \( 10^{69} \), the answer is:
none of them